Implementasi Elearning Efront Mendukung Sistem Perkuliahan Online Berbasis Web di Kampus STMIK Jakarta STI&K - Munich Heindari Ekasari; Eko Tri Asmoro (Jurnal Informatika Universitas Pamulang, 2020)
STMIK Jakarta STI&K is a computer campus in Indonesia. This campus has not optimally used online learning media. Electronic lecture is an online lecture medium, which allows students and lecturers to carry out lecture activities without having to meet physically. The current pandemic period requires academic activities to be carried out online. This electronic lecture media is widely available to be adopted to build an online lecture system in an institution. E-Learning Efront is an example of a system that can be used. Research on the inline lecture system can produce a system tailored to the needs applied at the STMIK Jakarta STI&K campus. The electronic lecture system using eFront can be changed according to user needs. To get good results from system development requires a good development stage according to the existing method. Development starts from planning until a good system implementation. One of the steps that can be done is to hold training and trials to measure the ability and understanding of system users. The evaluation stage is carried out by measuring and analyzing users interacting with the system. The e-learning implementation plan begins with the first preparation, then the resources are ready and the services and system infrastructure are available. Based on the results of the evaluation, decisions can be made regarding the application of e-learning at the STMIK Jakarta STI&K campus. The results of the implementation that have been carried out, it is found that the online lecture system is needed as an alternative in the use of information technology in the process of academic activities.